2021
DOI: 10.1590/0004-282x-anp-2020-0578
|View full text |Cite
|
Sign up to set email alerts
|

Does smoking impair sleep hygiene?

Abstract: Background: Sleep architecture and sleep hygiene might be disrupted by several pathogenetic mechanisms, and the effect of smoking has not been evaluated. Objective: To investigate the effect of smoking on sleep hygiene behaviors that might be associated with the deterioration of quality-of-life (QoL) parameters. Methods: In a prospective cross-sectional study, smokers (n=114) and nonsmokers (n=119) were included. The Pittsburgh Sleep Quality İndex (PSQI), the Epworth Daytime Sleepiness Scale (ESS), the Sleep H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Another survey suggest that smoking by itself is not associated with sleep quality 25 .The effect of smoking on sleep is currently mainly attributed to the excitatory effects of nicotine 26 .We can see that smoking is particularly deleterious to sleep quality. Addressing smoking stop to improve sleep may be a nice way to motivate student smokers to quit.…”
Section: Discussionmentioning
confidence: 92%
“…Another survey suggest that smoking by itself is not associated with sleep quality 25 .The effect of smoking on sleep is currently mainly attributed to the excitatory effects of nicotine 26 .We can see that smoking is particularly deleterious to sleep quality. Addressing smoking stop to improve sleep may be a nice way to motivate student smokers to quit.…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, poor sleep quality, along with several other unhealthy habits, have been associated with lower grey matter brain volume and although smoking was not a significant factor in the multivariate analysis [129], it has been associated with several neurological defects such as mild cognitive impairment, memory problems and even sudden deafness [15,27,130,131]. In addition, smoking combined with poor sleep quality have also been associated with mental health problems [55] such as anxiety, depression and bipolar disorder [22,46,51,132]. This has also been demonstrated in a genetic study, in which smoking and sleep quality were independent risk factors for both depression and bipolar disorder [16].…”
Section: Smoking Sleep and Other Medical Conditionsmentioning
confidence: 99%
“…On the other hand, there are also studies that have not identified significant relationships between cigarette smoking and sleep quality, apart from an indirect confounding action along with other socioeconomic factors [50], or merely an insignificant effect in sleep hygiene [51]. However, all the aforementioned studies used mainly questionnaires, whilst the detrimental effect of smoking on sleep quality has also been demonstrated with biochemical and genetic examinations.…”
Section: Smoking and Sleep Qualitymentioning
confidence: 99%